2017
DOI: 10.3233/cbm-160427
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-124-3p affects proliferation, migration and apoptosis of bladder cancer cells through targeting AURKA

Abstract: MiR-124-3p has significant impact on proliferation, migration and apoptosis of BC cells by targeting AURKA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 33 publications
2
29
0
Order By: Relevance
“…MiR-124, which was identified as a tumor suppressor, has been confirmed to be downregulated in cancers and investigated for its role in regulating cell proliferation and apoptosis by targeting different genes in distinct types of cancer [2830]. Moreover, miR-135b was identified as a biomarker for colorectal cancer [31] and reported to modulate apoptosis by targeting large tumor-suppressor kinase 2 [32].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-124, which was identified as a tumor suppressor, has been confirmed to be downregulated in cancers and investigated for its role in regulating cell proliferation and apoptosis by targeting different genes in distinct types of cancer [2830]. Moreover, miR-135b was identified as a biomarker for colorectal cancer [31] and reported to modulate apoptosis by targeting large tumor-suppressor kinase 2 [32].…”
Section: Discussionmentioning
confidence: 99%
“…Guo et al reported that AURKA overexpression in BCa was strongly associated with tumor stage and grade; additionally, AURKA upregulation was correlated with poor overall survival [81]. In xenograft BCa models, the therapeutic potential of AURKA blockade was demonstrated [82].…”
Section: The Hub Genes Potentially Associated With the Clinical Prognmentioning
confidence: 99%
“…The tumor suppressor miR-124 is downregulated in cancers and plays a role in regulating cell proliferation and apoptosis by targeting different genes in distinct types of cancer. 33,34 Gong et al also reported that the downregulation of miR-125b correlates with the upregulation of SP1, a key transcription factor involved in various types of diseases that plays vital roles in angiogenesis, inflammation, cell proliferation, migration/ invasion, and survival. 35,36 In summary, based on these previous studies and our results, we hypothesized that MALAT1 might play important roles in DR by regulating Sag and Guca1a through miR-124-3p and regulating Pde6g through miR-125b-5p.…”
Section: Discussionmentioning
confidence: 99%